24-Hour vs. Spot Urinary Sodium and Potassium Measurements in Adult Hypertensive Patients: A Cohort Validation Study. (27th June 2019) - Wan, Elizabeth R; Cross, Jennifer; Sofat, Reecha; Walsh, Stephen B
Abstract: BACKGROUND: Sodium intake is correlated with the development of hypertension. Guyton's principals suggest that the 24-hour urinary sodium excretion reflects sodium ingestion over the same period. 24-hour urine collections are arduous to collect, so many centers use spot urinary measurements instead. We compared spot to matched 24-hour urinary electrolyte measurements. METHODS: We examined 419 hypertensive patients from the UCL Complex Hypertension Clinic. 77 had matched and complete 24-hour and spot urinary and serum biochemistry to examine. We compared the spot and 24-hour urinary; sodium concentration, Na/Cr ratio, FENa, Kawasaki and Tanaka estimated sodium excretion as well as the potassium concentration, K/Cr ratio, Kawasaki and Tanaka potassium excretion. RESULTS: Our cohort was 58% male and the median age was 41 years. The 24-hour and spot Na concentrations correlated moderately ( r = 0.4633, P < 0.0001). The 24-hour and spot Na/creatinine ratios correlated weakly ( r = 0.2625, P = 0.0194). The 24-hour and spot FENa results showed a weak negative correlation ( r = −0.222, P = ns). The 24-hour sodium excretion and the Kawasaki-derived spot urine sodium excretion correlated moderately ( r = 0.3118, P = 0.0052). All Bland–Altman analyses showed poor agreement. The 24-hour and spot potassium concentrations correlated very poorly ( r = 0.1158, P = ns). The 24-hour and spot urinary K/creatinine ratios correlated weakly ( r = 0.47, P ≤ 0.0001). 24-hour and Kawasaki and Tanaka estimated potassium excretions correlated much better ( r = 0.58, P < 0.0001). CONCLUSIONS: Spot urinary measurements of sodium give a very poor understanding of the natriuresis occurring over the same 24-hour period. The Kawasaki and Tanaka estimations of the 24-hour sodium excretion showed a much lower correlation than previously reported.